Feeding Habits of the Mangrove Sesarmid Crab Neosarmatium trispinosum (Crustacea) in the Ryukyu Islands, Japan (The Agriculturists, 2010)
Sesarmid crabs are reported to dominate the Indo West-Pacific mangroves and consume huge amounts of mangrove leaves and detritus. Neosarmatium trispinosum Davie (1994) is common in the landward mangroves of the Ryukyu Islands in southern Japan. Stomach contents of the crabs collected from Okinawa, Miyako and Iriomote Islands showed that their diet consisted of mainly mangrove leaves with small amounts of sediments indicating that N. trispinosum is primarily detritivorous. The feeding preference of N. trispinosum was investigated by offering three types (green, yellow and brown) of Bruguiera gymnorrhiza leaves. Crabs were found to prefer brown leaves than the green or yellow ones. Consumption rate of brown leaves was significantly higher (p